Monte-Carlo calculations of evaporation and fission in excited spallation reaction fragments - Chatziioanidis, Panajiotis; Nicolis, Nikolaos (HNPS Advances in Nuclear Physics, 2024)
We report on a transcription of the Java program MCEF into FORTRAN. The program MCEF is suitable for fast Monte-Carlo calculations of the evaporation process and fission of highly excited fragments produced in spallation nuclear reactions. We studied the Java algorithm, analyzed the physics that govern the de-excitation process, converted the physics into FORTRAN functions, checked that the program’s fundamental functions work properly, and compared the program’s results to experimental data. The evaporation process translates well into the code, which has the advantage of being easily understood by the user, runs quickly, and is compatible with available related programs. Comparisons with the experimental data indicate the need for possible improvements and extensions of the present code.